THE HEAVIEST SENTENCING FOR THE LEGAL SUBJECT OF CORRUPTION CRIME PERPETRATOR - Oksidelfa Yanto (Jurnal Hukum Mimbar Justitia, 2022)
This study uses a normative juridical research method through literature study by collecting secondary data. In this study, it was found that the discussion about corruption never ends. Legal subjects that can be held accountable come one after another. The legal subject in this case is "any person who unlawfully commits an act of enriching himself or another person or a corporation that can harm state finances or the state economy." Regarding punishment for legal subjects who commit criminal acts of corruption, especially in certain circumstances, namely punishment toughest to death penalty.Keywords : Punishment, Legal Subject, Corruption.